2013
DOI: 10.3892/ijmm.2013.1604
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a salsolinol-like compound, the neurotoxin, 1-acetyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline, in a cellular model of hyperglycemia and a rat model of diabetes

Abstract: Abstract. There are statistical data indicating that diabetes is a risk factor for Parkinson's disease (PD). Methylglyoxal (MG), a biologically reactive byproduct of glucose metabolism, the levels of which have been shown to be increase in diabetes, reacts with dopamine to form 1-acetyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline (ADTIQ); this formation may provide further insight into the connection between PD and diabetes. In this study, we investigated the role of ADTIQ in these two diseases to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…This active metabolite is present in human brain tissue, including the substantia nigra. ADTIQ levels are increased in PD patients (Deng et al, 2012), and the structure of ADTIQ resembles that of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) elucidated using hyperglycemic cell and rat models (Song et al, 2014). Interestingly, in a separate study, ADTIQ has been shown as an endogenous neurotoxin in SH-SY5Y neuroblastoma cells, and the levels of both MGO and ADTIQ are increased in the striatum of a streptozotocin-induced diabetic rat model (Xie et al, 2015).…”
Section: Modeling the Influence Of Ages In Neurodegenerative Diseasesmentioning
confidence: 99%
“…This active metabolite is present in human brain tissue, including the substantia nigra. ADTIQ levels are increased in PD patients (Deng et al, 2012), and the structure of ADTIQ resembles that of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) elucidated using hyperglycemic cell and rat models (Song et al, 2014). Interestingly, in a separate study, ADTIQ has been shown as an endogenous neurotoxin in SH-SY5Y neuroblastoma cells, and the levels of both MGO and ADTIQ are increased in the striatum of a streptozotocin-induced diabetic rat model (Xie et al, 2015).…”
Section: Modeling the Influence Of Ages In Neurodegenerative Diseasesmentioning
confidence: 99%
“…MGO increased the levels of DA and Sal, contributing to neuronal cell death [76]. Moreover, the elevated levels of ADTIQ and MGO were observed in the cell model of hyperglycemia and the brains of rats with diabetes [77]. Figure 2 showed significantly increased levels of ADTIQ and MGO in the striatum of SD rats with type2 diabetes.…”
Section: Adtiq Is a Link Between Pd And Diabetesmentioning
confidence: 94%
“…ADTIQ not only accumulates in PD brains but also mimics the effects of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) whose effects on mitochondria resemble the changes associated with PD [69]. Further evidence supporting the proposed link between MG, dopamine and generation of the neurotoxin ADTIQ is shown by the increased levels of glycolytic enzymes, MG and ADTIQ in the brains of diabetic rats [70]. It may be relevant to note that another group of nigrostriatal neurotoxins, N-methylated-beta-carboline and 2,9-dimethyl beta-carboline, whose structures resembles MPTP, not only inhibit mitochondria respiration but are also potent inhibitors of triosephosphate isomerase (TPI) [71].…”
Section: Methylglyoxal and Pdmentioning
confidence: 99%
“…Furthermore, in the substantia nigra increased MG generation would (as previously mentioned) following reaction with dopamine, increase the likelihood of formation of ADTIQ, which has been detected in diabetic brains, which in turn will damage mitochondria etc. and further exacerbate the condition, to promote a self-reinforcing deleterious cycle of dysfunction [70,101]. …”
Section: Aging Proteostatic Dysfunction and Pdmentioning
confidence: 99%